Association of handgrip strength and walking pace with incident Parkinson's disease - Mengyi Liu; Panpan He; Ziliang Ye; Yuanyuan Zhang; Chun Zhou; Sisi Yang; Yanjun Zhang; Xianhui Qin (Wiley, 2024)
Abstract Background We aimed to quantify the association of handgrip strength and self‐reported walking pace with incident Parkinson's disease (PD) in the general population. Methods A total of 419 572 participants (54.1% females, mean age: 56.1 years [SD, 8.2]) without prior PD were included from UK Biobank. Handgrip strength was assessed by dynamometer. Walking pace was self‐reported as slow, average or brisk. The study outcome was incident PD, determined by self‐report data, hospital admission records or death records. Results The mean handgrip strength was 23.5 (SD, 6.3) and 39.6 (SD, 8.9) kg for females and males, respectively. A total of 33 645 (8.0%), 221 682 (52.8%) and 164 245 (39.2%) participants reported slow, average and brisk walking pace, respectively. Over a median follow‐up duration of 12.5 years, 2152 participants developed incident PD. When handgrip strength was assessed as sex‐specific tertiles, compared with those in the third tertile, the adjusted hazard ratios (HRs) (95% confidence interval [CI]) of incident PD for participants in the second and first tertiles were 1.23 (1.09-1.39) and 1.60 (1.42-1.79), respectively. Compared with brisk walking pace, average (HR, 1.33; 95% CI: 1.20-1.47) or slow (HR, 1.84; 95% CI: 1.57-2.15) walking pace was associated with a higher risk of incident PD. A lower grip strength (Tertiles 1 and 2) and an average/slow walking pace accounted for 23.8% and 19.9% of PD cases, respectively. When handgrip strength and walking pace were considered together, the highest risk of incident PD was observed in participants with both lowest handgrip strength and slow walking pace (HR, 2.89; 95% CI: 2.30-3.64). Genetic risks of PD did not significantly modify the relation of handgrip strength (P for interaction = 0.371) or walking pace (P for interaction = 0.082) with new‐onset PD. Conclusions Low handgrip strength and slow walking pace were significantly associated with a higher risk of incident PD, regardless of the individuals' genetic risk profile.